Development of Goods Carrier Robots and Interaction of COVID-19 Patients with Medical Personnel at Politeknik Negeri Jember - Dewanto, W K; Widiawan, B; Setyohadi, D P S; Surateno; Mashfukh, M (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
Covid-19 virus is the first type of deadly virus found in wuhan city, China. Based on worldometer data that entered until August 25, 2020, in Indonesia, 157,859 people were positively infected with the Covid-19 virus. The increasing number of infected patients is at high risk to nurses and doctors because one of the causes of the infection is by direct contact with patients who are declared positive there is a corona virus. CNN Indonesia on August 25, 2020 recorded as many as 90 medical personnel killed from exposure to the Covid-19 virus. To reduce the risk of coronavirus spreading in nurses or doctors when carrying out the task of treating patients in hospitals or health facilities, Politeknik Negeri Jember designed the manufacture of robots that can bring medical needs or needs of patients to the treatment room. this aims to reduce direct contact between patients and medical personnel. Remote control based on keyboard with radio telemetry is expected to prevent physical contact between medical personnel and patients. So the chances of exposure to the Covid-19 virus are less. The use of an interface in the form of streaming video calls, allows patients to communicate directly with a nurse or doctor (telehealth).